An Information Security Strategy for Networkable Devices. - Oshri, I.
Networkable Windows-based operating system devices present information security challenges to both vendors and users of such devices. This article highlights some of those threats and offers measures to improve the link between a firm's business strategy, its operational activities, and its information security strategy.
Keywords: Firm business strategy; Information security strategy; Networkable Windows-based operating system device